An Efficient Medium Access Control (MAC) Forwarding Technique for Multihop Network - Gannapathy, Vigneswara Rao; Suaidi, Mohd Kadim; Johal, Muhammad Syahrir; Fayeez, Ahamed Tuani Ibrahim; Siva Kumar, Subramaniam; Ranjit, S.S.S. (2012)
The function of Medium Access Control (MAC) protocol in network communication is to efficiently facilitate the use of available channels when more nodes (i.e. laptop, PC, smart phones and etc) involving in transmission activity in the network. The protocol uses the well-known Carrier Sense Multiple Access with Collision Avoidance (CSMA/CA) mechanism to allow all nodes in the network to communicate between each other without collision. This mechanism has been standardized in IEEE 802.11 and it is proven to provide the better performance of throughput for single hop communication. The node which is uses CSMA/CA mechanism will perform a handshake (the exchange of RTS and CTS signalling packets) prior initiates any packet transmission. The handshake is very crucial in order to avoid the collision caused by simultaneously transmission to the single receiver. However, this mechanism undergoes bad throughput performance when directly implemented for multihop communication. The reason behind this poor performance is due to the inefficient forwarding in CSMA/CA mechanism which is caused larger signalling overheads. The exchange of RTS and CTS signalling that required at each hop throughout the multihop network eventually will cause the larger overheads and throughput degradation. Therefore, an efficient forwarding operation is proposed in this work to reduce the signalling overheads and ultimately allows a smooth forwarding of packet in the multihop network without any collision. In this work, the multihop network performances are evaluated analytically in terms of throughput and overhead. Through the simulation, it is proven that the proposed forwarding technique provides significant improvement in throughput and overhead.